Association of Intraoperative Ventilator Management With Postoperative Oxygenation, Pulmonary Complications, and Mortality. (January 2020) - Douville, Nicholas J.; Jewell, Elizabeth S.; Duggal, Neal; Blank, Ross; Kheterpal, Sachin; Engoren, Milo C.; Mathis, Michael R.
Abstract : BACKGROUND: "Lung-protective ventilation" describes a ventilation strategy involving low tidal volumes (VT s) and/or low driving pressure/plateau pressure and has been associated with improved outcomes after mechanical ventilation. We evaluated the association between intraoperative ventilation parameters (including positive end-expiratory pressure [PEEP], driving pressure, and VT ) and 3 postoperative outcomes: (1) PaO2 /fractional inspired oxygen tension (FIO2 ), (2) postoperative pulmonary complications, and (3) 30-day mortality. METHODS: We retrospectively analyzed adult patients who underwent major noncardiac surgery and remained intubated postoperatively from 2006 to 2015 at a single US center. Using multivariable regressions, we studied associations between intraoperative ventilator settings and lowest postoperative PaO2 /FIO2 while intubated, pulmonary complications identified from discharge diagnoses, and in-hospital 30-day mortality. RESULTS: Among a cohort of 2096 cases, the median PEEP was 5 cm H2 O (interquartile range = 4–6), median delivered VT was 520 mL (interquartile range = 460–580), and median driving pressure was 15 cm H2 O (13–19). After multivariable adjustment, intraoperative median PEEP (linear regression estimate [B] = −6.04; 95% CI, −8.22 to −3.87; P < .001), median FIO2 (B = −0.30; 95% CI, −0.50 to −0.10; P = .003), and hours with driving pressure >16 cm H2 O (B = −5.40; 95% CI, −7.2 to −4.2; P < .001) were associated with decreased postoperative PaO2 /FIO2 . Higher postoperative PaO2 /FIO2 ratios were associated with a decreased risk of pulmonary complications (adjusted odds ratio for each 100 mm Hg = 0.495; 95% CI, 0.331–0.740; P = .001, model C-statistic of 0.852) and mortality (adjusted odds ratio = 0.495; 95% CI, 0.366–0.606; P < .001, model C-statistic of 0.820). Intraoperative time with VT >500 mL was also associated with an increased likelihood of developing a postoperative pulmonary complication (adjusted odds ratio = 1.06/hour; 95% CI, 1.00–1.20; P = .042). CONCLUSIONS: In patients requiring postoperative intubation after noncardiac surgery, increased median FIO2, increased median PEEP, and increased time duration with elevated driving pressure predict lower postoperative PaO2 /FIO2 . Intraoperative duration of VT >500 mL was independently associated with increased postoperative pulmonary complications. Lower postoperative PaO2 /FIO2 ratios were independently associated with pulmonary complications and mortality. Our findings suggest that postoperative PaO2 /FIO2 may be a potential target for future prospective trials investigating the impact of specific ventilation strategies for reducing ventilator-induced pulmonary injury.